THE EFFECT OF USING SONG TO THE STUDENTS’ MASTERY OF PRESENT TENSE - Hartiwi, Juni; Nurdianti, Desti; Maiza, Masfa; Dewi, Nila Sari; Sutiwi, Sri (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT The low mastery of grammar, especially Present Tense, and low learning motivation are the background of this study, where seventh grade students of SMP Nurul Islam consider grammar as a difficult and boring material. The focus of this study is to test the effectiveness of using song media as an innovative strategy to improve students' mastery of Present Tense. As an important step, this study uses the Classroom Action Research (CAR) method which is implemented in two cycles on 32 students. Each cycle includes the stages of planning, action, observation, and reflection, with data collection through pre-test, post-test, observation sheets, and questionnaires. The main findings show a significant improvement in student learning outcomes. The average student score increased from 7.1 in the pre-test to 8.8 in the post-test of the second cycle, with 100% of students successfully achieving the completion criteria. In addition, the use of songs successfully created a more enjoyable learning atmosphere and increased student active participation. In conclusion, the use of song media has proven to be an effective strategy in improving students' mastery of Present Tense, both from the cognitive and affective aspects.   ABSTRAK Rendahnya penguasaan tata bahasa, khususnya Present Tense, serta motivasi belajar yang rendah menjadi latar belakang penelitian ini, di mana siswa kelas VII SMP Nurul Islam menganggap grammar sebagai materi yang sulit dan membosankan. Fokus penelitian ini adalah untuk menguji efektivitas penggunaan media lagu sebagai strategi inovatif untuk meningkatkan penguasaan Present Tense siswa. Sebagai langkah penting, penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus pada 32 siswa. Setiap siklus mencakup tahapan perencanaan, tindakan, observasi, dan refleksi, dengan pengumpulan data melalui pre-test, post-test, lembar observasi, dan kuesioner. Temuan utama menunjukkan adanya peningkatan yang signifikan pada hasil belajar siswa. Nilai rata-rata siswa meningkat dari 7,1 pada pre-test menjadi 8,8 pada post-test siklus kedua, dengan 100% siswa berhasil mencapai kriteria ketuntasan. Selain itu, penggunaan lagu berhasil menciptakan suasana belajar yang lebih menyenangkan dan meningkatkan partisipasi aktif siswa. Kesimpulannya, penggunaan media lagu terbukti menjadi strategi yang efektif dalam meningkatkan penguasaan Present Tense siswa, baik dari aspek kognitif maupun afektif.